2009
DOI: 10.1007/s11186-009-9086-4
|View full text |Cite
|
Sign up to set email alerts
|

Time orientations and emotion-rules in finance

Abstract: This article explores how Anglo-American financial firms since the 1980s have operated and acted in an increasingly deregulated, risky, and uncertain arena. I look at these firms and their actions with a particular focus on "temporality" and requisite "emotion-rules," where variations in emotion-rules correspond with organizational definitions of uncertainty. Firms impose specific emotion-rules, depending on national policies, official duties, and interpretations of each risk. In finance, caveat emptor (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…People trading on the Paris Stock Exchange in the late 1990s routinely displayed the full range of human emotions (Hassoun 2006), an ethnographic observation consistent with the psychological evidence of Lo et al's (2005) analysis of day traders and Lo & Repin's (2002) physiological evidence. According to Pixley (2009), financial organizations operate with emotion rules that stipulate appropriate attitudes and comportment for personnel (including the supreme self-confidence noted by Ho 2009). Abolafia (2005) analyzed the transcripts of the meetings of the Federal Open Market Committee (FOMC), the chief policymaking body of the Federal Reserve System.…”
Section: Micro Contexts For Macro Financementioning
confidence: 99%
“…People trading on the Paris Stock Exchange in the late 1990s routinely displayed the full range of human emotions (Hassoun 2006), an ethnographic observation consistent with the psychological evidence of Lo et al's (2005) analysis of day traders and Lo & Repin's (2002) physiological evidence. According to Pixley (2009), financial organizations operate with emotion rules that stipulate appropriate attitudes and comportment for personnel (including the supreme self-confidence noted by Ho 2009). Abolafia (2005) analyzed the transcripts of the meetings of the Federal Open Market Committee (FOMC), the chief policymaking body of the Federal Reserve System.…”
Section: Micro Contexts For Macro Financementioning
confidence: 99%
“…As in previous research on finance and emotions (see, e.g. Pixley [2009]; Shapiro [2012]), trust is explicitly stated to be of paramount importance in OECD arguments for the necessity of financial education. According to the OECD (2013, 11), financial education is "critical to restore trust and confidence in the financial system, promote financial stability and provide the necessary public backing to financial reforms."…”
Section: Trust In Financementioning
confidence: 77%
“…In addition, emotions convey information that humans would be unable to gather or assess through their cognitive faculties alone (Morton 2010); they motivate, direct, and orient attention and action in complex dialectics between thinking, feeling, and doing. As argued by Barbalet (2001, 60), there is no such thing as non-emotional actioneven instrumental rationality relies on "particular facilitating emotions which function to motivate instrumental action, such as pride in one's expertise and skill, satisfaction in one's work, distaste for waste of material and time" (Barbalet 2001;Pixley 2009). In the financial sphere, for example, Pixley's (2004Pixley's ( , 2009Pixley's ( , 2012 research has shown that firms rely on emotions of trust and distrust to make decisions while facing future complexity and uncertainty.…”
Section: Financial Rationality Subjectivity and Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly since credit ‘froze’, more people admit something approximating my thesis that emotions like trust provide stability to fraught decisions that are invariably leaps into the unknown. Indeed, rationalisations before and after in organisational forms are often more deceptive and destabilising than emotions, and thus ‘rational choice’ is implausible in facing uncertainty, and so is the idea of irrational anomalies (see Pixley 2004, 2009).…”
Section: Assessing These Proposalsmentioning
confidence: 99%